2018
DOI: 10.1111/jrh.12337
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Literacy and Outcomes in Rural Wisconsin Adults

Abstract: Purpose Low oral health literacy (OHL) is an emerging risk factor for several oral health outcomes, but there are very few studies of OHL overall and no studies of OHL in the rural United States. The purpose of this study was to examine the association between OHL and sociodemographic factors, as well as several oral health outcomes, in rural adults served by an integrated medical and dental care system in Wisconsin. Methods A cross‐sectional survey was administered to a stratified random sample of patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Association of lower health literacy with a higher chance of suffering from gingivitis or ill oral health is in accordance with many studies reporting similar associations of patients with low health literacy and their low general health status or having other health issues compared to patients with higher health literacy [14][15][16]. Our results are also consistent with studies on oral health issues and health literacy, even though these types of studies are scarce [17][18][19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Association of lower health literacy with a higher chance of suffering from gingivitis or ill oral health is in accordance with many studies reporting similar associations of patients with low health literacy and their low general health status or having other health issues compared to patients with higher health literacy [14][15][16]. Our results are also consistent with studies on oral health issues and health literacy, even though these types of studies are scarce [17][18][19].…”
Section: Discussionsupporting
confidence: 92%
“…In health research, it was found that poor health literacy is associated with a wide range of health-related results, including poorer health, poorer use of preventive health care, higher mortality and more hospitalizations [14][15][16]. Although research of oral health and health literacy is not sufficient, there are few studies showing positive association of higher HL with better periodontal health [17], and associations of lower HL with untreated caries, less frequent tooth brushing and irregular flossing [18], fewer visits to the dentist and more frequent emergency room visits for nontraumatic dental conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence has demonstrated that income, education, and self-rated oral health are important predictors of OHL across different populations. [29][30][31] The associations between tooth loss, education, and self-rated oral health have also been largely documented in the literature. [32][33][34][35] Similar to our findings, previous studies indicate that income and self-rated oral health are important predictors of dental service utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that adults in the more rural areas in the United States were 65% less likely to have received a preventive dental procedure than their urban counterparts. In addition to the shortage of dental professionals, 3 other factors that could account for these results include rural residents not prioritizing oral health as a result of other needs taking precedence such as food security among those with lower SES, 26 as well as limited health literacy, 27 or negative attitudes and perceived lack of need 27 . A need for transportation could be another barrier 28 .…”
Section: Discussionmentioning
confidence: 99%